Anti-Osteogenic Effect of Danshensu in Ankylosing Spondylitis: An in Vitro Study Based on Integrated Network Pharmacology - Li, Jiaxiao; Chen, Zexin; Liao, Hongbo; Zhong, Yanting; Hua, Junying; Su, Miaoling; Li, Jiahao; Xu, Jinrong; Cui, Liao; Cui, Yang (Frontiers in Pharmacology, 2021)
Ankylosing spondylitis (AS) is a chronic inflammatory disease characterized by abnormal bone metabolism, with few effective treatments available. Danshensu (3-[3,4-dihydroxy-phenyl] lactic acid) is a bioactive compound from traditional Chinese medicine with a variety of pharmacologic effects. We previously showed that salvianolic acid B, another bioactive component of Salvia miltiorrhiza, promoted osteogenic differentiation of normal human mesenchymal stem cells. In the present study, we investigated the pharmacologic effect and molecular mechanism of Danshensu in AS. Potential targets of Danshensu were identified in the Bioinformatics Analysis Tool for Molecular Mechanism of Traditional Chinese Medicine, Traditional Chinese Medicine Systems Pharmacology, Swiss Target Prediction, and Pharmamapper databases; and potential pharmacologic target genes in AS were identified in the Online Mendelian Inheritance in Man, GeneCards, and DisGeNET databases. Differentially expressed genes related to AS were obtained from the Gene Expression Omnibus database. Overlapping targets of Danshensu and AS were determined and a disease–active ingredient–target interaction network was constructed with Cytoscape software. Gene Ontology and Kyoto Encyclopedia of Genes and Genomes pathway enrichment analyses of the common targets were performed using Bioconductor. To test the validity of the constructed network, an in vitro model was established by treating osteoblasts from newborn rats with low concentrations of tumor necrosis factor (TNF)-α. Then, the in vitro model and AS fibroblasts were treated with Danshensu (1–10 μM). Osteogenesis was evaluated by alkaline phosphatase staining and activity assay, alizarin red staining, quantitative PCR, and western blotting. We identified 2944 AS-related genes and 406 Danshensu targets, including 47 that were common to both datasets. The main signaling pathways associated with the targets were the c-Jun N-terminal kinase (JNK) and extracellular signal-regulated kinase (ERK) pathways. A low concentration of TNF-α (0.01 ng/ml) promoted the differentiation of osteoblasts; this was inhibited by Danshensu, which had the same effect on AS fibroblasts but had the opposite effect on normal osteoblasts. Danshensu also decreased the phosphorylation of JNK and ERK in AS fibroblasts. There results provide evidence that Danshensu exerts an anti-osteogenic effect via suppression of JNK and ERK signaling, highlighting its therapeutic potential for the treatment of AS.